FITUR KESALAHAN PENGGUNAAN EJAAN DALAM SURAT DINAS DI UNIVERSITAS - Emmy Erwina; Hendra Mulia (STKIP Siliwangi, 2023)
This study aims to get an overview of the features of spelling errors in the preparation of official letters and to find out the factors that cause written language errors in official letters at one of the universities in Medan City. The procedure of this study uses a qualitative descriptive analysis procedure. The data collection method in this study is in the form of a documentary method. The information analysis method uses language error analysis procedures, namely information identification, information classification, and determining the frequency of errors. The source of information for this research is in the form of official letters written at one of the universities in Medan City. Research information in the form of written language that contains spelling errors. The research results show that there are errors in the use of spelling, and these errors are listed in interlanguage errors, such as language transfer and transfer of training. The low ability of the Indonesian language writer of the letter is the cause of language errors. The results of this research can help other agencies to pay more attention to the use of the Indonesian language, and it is considered important to hold official letter-writing training by authorized institutions.